Human biomonitoring of multiple mycotoxins in the Belgian population: Results of the BIOMYCO study. (November 2015) - Heyndrickx, Ellen; Sioen, Isabelle; Huybrechts, Bart; Callebaut, Alfons; De Henauw, Stefaan; De Saeger, Sarah
Abstract: Mycotoxins are important food contaminants responsible for health effects such as cancer, nephrotoxicity, hepatotoxicity or immunosuppression. The assessment of mycotoxin exposure is often based on calculations combining mycotoxin occurrence data in food with population data on food consumption. Because of limitations inherent to that approach, the direct measurement of biomarkers of exposure in biological fluids has been proposed as a suitable alternative to perform an accurate mycotoxin exposure assessment at individual level. For this reason, the BIOMYCO study was designed to assess mycotoxin exposure in Belgian adults and children using urinary biomarkers of exposure. Morning urine was gathered in a representative part of the Belgian population according to a standardised study protocol, whereby 155 children (3–12 years old) and 239 adults (19–65 years old) were selected based on random cluster sampling. These urine samples were analysed for the presence of 33 potential biomarkers with focus on aflatoxins, citrinin (CIT), fumonisins, trichothecenes, ochratoxin A (OTA), zearalenone and their metabolites using two validated LC–MS/MS methods. Nine out of the 33 analysed mycotoxins were detected whereby deoxynivalenol (DON), OTA, CIT and their metabolites were the most frequently detected. Deoxynivalenol-15-glucuronide was the main urinary DON biomarker and was found in all urine samples in the ng/mL range. Furthermore deoxynivalenol-3-glucuronide was quantified in 91% of the urine samples collected from children and in 77% of the samples collected from adults. Deoxynivalenol was detected in 70% and 37% of the samples of children and adults respectively. For the first time deepoxy-deoxynivalenol-glucuronide was detected in children's urine (17%). In the samples collected by adults, the prevalence was 22%. Whereas all these mycotoxins contaminated the urine samples in the ng/mL range, CIT and OTA were present in much lower concentrations (pg/mL). OTA contaminated 51% and 35% of the samples collected by children and adults respectively. CIT and its metabolite were present in 72% and 6% of children's urine, whereas they contaminated 59% and 12% of adult's urine. Finally, α-zearalenol and β-zearalenol-14-glucuronide were found in respectively one and two samples from adults. The exposure to DON, OTA and CIT was compared between subgroups and urinary mycotoxin concentrations differed significantly among age and gender. Based on the urinary levels, the daily intake of DON and OTA was estimated and evaluated whereby, depending on the used method, 16–69% of the population possibly exceeded the tolerable daily intake for DON and 1% for OTA. The BIOMYCO study is the first study whereby a multi-toxin approach was applied for mycotoxin exposure assessment in adults and children on a large-scale. Moreover, it is the first study that described the exposure to an elaborated set of mycotoxins in the Belgian population. Biomarker analysis showed a clear exposure of a broad segment of the Belgian population to DON, OTA and CIT. The risk assessment based on these data indicates a potential concern for a number of individuals whereby young children need special attention because of the relatively higher food intake per kg body weight. Highlights: Morning urine of 394 Belgian individuals was collected according to a standardised study protocol. Deoxynivalenol, ochratoxin A, citrinin and their metabolites were the most frequently detected. Deoxynivalenol-15-glucuronide was the main urinary DON biomarker found. For the first time deepoxy-deoxynivalenol-glucuronide was detected in children's urine. Risk assessment based on urinary levels indicates a potential concern for a number of individuals.